Critical practice lens for economic and Government Transformation Programmes - Han, Chun Kwong (Universiti Putra Malaysia Press, 2013)
“TRANSFORMATION” has been a recurring pervasive principle and nametag among all the Malaysian public sector initiatives — beginning with the Multimedia Super Corridor in the mid-1990s, then the knowledge-based and innovation economies, and subsequently the regional development corridors in the 2000s. In the last two years, however, the Government has been taking a radically new approach to national transformation. The Government Transformation Programme was initiated in 2009, followed by the New Economic Model and Economic Transformation Programme in 2010. More recently, new programmes were started in the areas of political and rural transformation. Presently, transformation can be perceived as the inception stage, as the various programmes will be undergoing a long continuous implementation journey into 2020. In order to make a real significant change to the condition of the Rakyat, the transformation needs to be driven from a synthesis of economic, managerial, organizational, social and technological dimensions at the multiple levels of the individual, organization, industry, government, society and nation. We offer another way of seeing and doing transformation using an enhanced critical theory and critical practice. We define critical practice as an iterative reflexive process, firstly by developing knowledge-for-understanding from a sophisticated model of reality. Secondly, we provide a critique of underpinning assumptions and presumptions whereby the constraining conditions of the status quo and emancipation become knowable and explicit, that is, knowledge-for- evaluation. Finally, we re-create, re-define, re-design, re-imagine, re-invent and re-vision the pragmatic, doable and implementable programmes from knowledge-for-action. We re-define the concept of “Doing and Being” whereby Yin meets Yang in critical practice of the economic, government, political and social transformation initiatives to transform Malaysia into a high-income developed country by 2020.